Penegakan Diagnosis dan Tatalaksana Keratitis Bakterial - Devina Hardianto; Devira Fitriani Kamal; Mochamad Fauzan Dava; Rani Himayani; Putu Ristyaning Ayu Sangging (Medula, 2023)
Bacterial keratitis is an infection of the cornea that caused by the invasion and proliferation of bacteria in the cornea, which can cause ulceration of the cornea. Bacterial keratitis is most often caused by Staphylococcus aureus, Staphylococcus epidermis, Streptococcus pneumoniae, and Pseudomonas aeruginosa. The use of contact lenses is associated with the incidence of bacterial keratitis. Other risk factors are alcohol, malnutrition, trauma, changes in the surface of the cornea. Symptoms that are often experienced are pain and red eyes, blurred vision, sensitivity to light, watery eyes, and tearing, because of damage in corneal epithelium and stromal inflammation due to the entry of bacteria. It is necessary to establish the diagnosis of bacterial keratitis. Evaluation is by inspection of the eye using slit lamp. Conjunctival injection, white infiltrate on the cornea due to damage to the corneal epithelium can be found. In addition, corneal thinning, stromal edema, inflammatory endothelial plaques, folds of Descemet's membrane, mucopurulent discharge, and anterior chamber hypopyon were also found. Laboratory test is through a scraping of the cornea for gram staining or bacteria culture. The treatment of bacterial keratitis is using broad-spectrum antibiotics before culture test and definitive antibiotics after the causative bacteria are identified.